Algorithms for the management of scars: the importance of systematizing behaviors - Francisco Felipe Góis de Oliveira; Nathalia Moreira De Almeida França; Elvio Bueno Garcia; Leila Blanes; Alessandra Haddad (Revista Brasileira de Cirurgia Plástica)
Introduction: Pathological scars occur from the hyperproliferation of fibroblasts and can be classified into hypertrophic scars and keloids. Basically, hypertrophic scars do not grow beyond the limits of the original wound, while keloids grow horizontally in a nodular form. Despite the diversity of instruments used to guide the prevention, treatment and follow-up of pathological scars, there is a need for instruments that address local realities. The objective is to carry out a narrative review of the literature on scar management algorithms and create an updated algorithm. Methods: Descriptive study of narrative literature review, with a search in PubMed, SciELO, LILACS, MEDLINE and Cochrane databases, from November 2010 to November 2020, published in English, Portuguese and Spanish. The descriptors used were: “cicatrix,” “keloid,” “algorithms,” and “wound healing.” The sample selection consisted of identifying the articles, reading the titles and abstracts, and selecting studies related to the topic. Subsequently, the full reading of the selected studies and classification according to the eligibility criteria were carried out. Results: 209 articles were found, and 116 were eliminated due to duplicity, resulting in 45 articles. A total of 8 articles that met the inclusion criteria were identified. Four articles were excluded after analysis and consensus meeting due to the absence of algorithms with scientific rigor; this study is composed of four articles. Conclusion: Four algorithms were found in the literature review that resulted in the development of an updated algorithm for scars.